Antibiotic action and resistance: updated review of mechanisms, spread, influencing factors, and alternative approaches for combating resistance - Halawa, Esraa M.; Fadel, Mohamed; Al-Rabia, Mohammed W.; Behairy, Ali; Nouh, Nehal A.; Abdo, Mohamed; Olga, Rada; Fericean, Liana; Atwa, Ahmed M.; El-Nablaway, Mohammad; Abdeen, Ahmed (Frontiers in Pharmacology, 2024)
Antibiotics represent a frequently employed therapeutic modality for the management of bacterial infections across diverse domains, including human health, agriculture, livestock breeding, and fish farming. The efficacy of antibiotics relies on four distinct mechanisms of action, which are discussed in detail in this review, along with accompanying diagrammatic illustrations. Despite their effectiveness, antibiotic resistance has emerged as a significant challenge to treating bacterial infections. Bacteria have developed defense mechanisms against antibiotics, rendering them ineffective. This review delves into the specific mechanisms that bacteria have developed to resist antibiotics, with the help of diagrammatic illustrations. Antibiotic resistance can spread among bacteria through various routes, resulting in previously susceptible bacteria becoming antibiotic-resistant. Multiple factors contribute to the worsening crisis of antibiotic resistance, including human misuse of antibiotics. This review also emphasizes alternative solutions proposed to mitigate the exacerbation of antibiotic resistance.